Students' Mathematical Problem Solving Ability In Faraidh - Noviani, Julia; Hakim, Hilda (Jumper: Journal of Educational Multidisciplinary Research, 2022)
Problem solving ability is a process to find a combination of a number of rules that can be applied in an effort to overcome new situations. This study aims to describe students' mathematical problem solving in faraidh. This study uses a qualitative approach. The subjects in this study consisted of 3 people with high, medium and low mathematical abilities. The instrument used is a faraidh problem-solving test in the form of fractional questions and interviews. Data analysis was carried out to describe students' ability in problem solving supported by test and interview results, followed by drawing conclusions. Based on the results of the study, subjects with high abilities had good problem solving skills on faraidh problems, as evidenced by all stages of problem solving that were met by highly skilled subjects starting from answering questions and interviews. Moderately capable subjects have sufficient problem-solving skills on the faraidh problem, it is proven that the subject is not right in solving problem solving and the subject does not properly explain problem solving. Low-ability subjects have sufficient problem-solving skills on the faraidh problem, it is proven that the subject has not been able to explain problem solving.